Pengaruh Profitabilitas, Solvabilitas, Dan Arus Kas Investasi Terhadap Harga Saham Farmasi - Nabilah Az Zahra; Dewa Putra Khrisna Mahardika (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The pharmaceutical industry has quite high competition in maximing company performance in order to attract investors. The aim of this study is to ascertain the solvency, profitability, and investment cash flow in influencing the company's stock price of pharmaceutical industry companies listed on the Indonesia Stock Exchange in 2017-2021. The method used is panel data regression analysis. The method used is a case study with descriptive research type and panel data regression analysis. The findings of this study reveal the profitability, solvency, and investment cash flows exert a substantial impact on stock prices simultaneously. Partially, the profitability, solvency and investment cash flow variables do not exhibit any noteworthy significanceeffect on the pharmaceutical industry stock prices for the 2017-2021 period. In conclusion, when viewed partially, all of the variables do not affect stock prices. Based on the research, for further enrich the study ti subsequent researchers to incorporate additional variables, change the research object, and increase the research period.